2018
DOI: 10.1515/intag-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting daily meteorological time series using ARIMA and regression models

Abstract: The daily air temperature and precipitation time series recorded between January 1, 1980 and December 31, 2010 in four European sites (Jokioinen, Dikopshof, Lleida and Lublin) from different climatic zones were modeled and forecasted. In our forecasting we used the methods of the Box-Jenkins and Holt- Winters seasonal auto regressive integrated moving-average, the autoregressive integrated moving-average with external regressors in the form of Fourier terms and the time series regression, including trend and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 10 publications
0
50
0
2
Order By: Relevance
“…A study by Unnikrishnan et al(2018) on forecasting weather parameters showed that ARIMA (011) (011) is the most commonly fitted ARIMA model for seasonal parameters. Similar study by Murat et al (2018) on forecasting meteorological time series data found that ARIMA models is best fit for air temperature studies. In the study by El-Mallah and Elsharkawy (2016) on time series modelling and short term forecast of yearly temperature disclosed that the quadratic ARIMA model and linear ARIMA model had the best overall performance in making short-term forecasts of yearly total temperature in Libya.…”
mentioning
confidence: 57%
“…A study by Unnikrishnan et al(2018) on forecasting weather parameters showed that ARIMA (011) (011) is the most commonly fitted ARIMA model for seasonal parameters. Similar study by Murat et al (2018) on forecasting meteorological time series data found that ARIMA models is best fit for air temperature studies. In the study by El-Mallah and Elsharkawy (2016) on time series modelling and short term forecast of yearly temperature disclosed that the quadratic ARIMA model and linear ARIMA model had the best overall performance in making short-term forecasts of yearly total temperature in Libya.…”
mentioning
confidence: 57%
“…The seasonal ARIMA (p,d,q) (P,D,Q) m process, also referred to as SARIMA (p,d,q) (P,D,Q) m is given by [7,35]:…”
Section: Methodsmentioning
confidence: 99%
“…Its main aim is to carefully and rigorously study the past observations of a time-series to develop an appropriate model which can predict future values for the series. It has three control constants (trend, seasonal, and irregular influence), which can control and manage influence of time segmentation through the specific time duration [7]. The ARIMA models are now widely used for various applications, such as natural environment [8][9][10][11], medicine [12], and engineering [13,14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The content of mineral nitrogen in the soil is also impacted by the biological activity of the soil, which in turn may be influenced by soil moisture (Wnuk et al, 2017) or N fertilization (Walkiewicz et al, 2018), and by atmospheric conditions. For this reason, research concerning the spatio-temporal variability of meteorological series from different climate zones Hoffmann et al, 2017;Krzyszczak et al, 2017a;2017b;2019) and their prediction (Murat et al, 2018) is extremely important. It allows for the assessment of the likely impact of climate change not only on agricultural production, but also on the content of macroelements (NPK) in the soil.…”
Section: Introductionmentioning
confidence: 99%